Queering Queer Spaces - Spencer Hardy; Juniper Monypenny (Voices, 2019)
As community spaces for LGBTQ+ individuals continue to expand and evolve, a variety of music and art-based programs have begun to develop. The potential for creative arts therapists to cultivate and expand these programs is without question. This article seeks to present one such program targeted towards transgender, nonbinary, gender creative, and questioning youth, age 10-14, who are seeking support in navigating their gender identity and the challenges of identifying outside of the “norm” of cisgender. Finding ourselves at a crossroads between traditional clinical mental health services and community-based approaches, we discuss the intentionality behind “queering” our program development as well as a spectrum of challenges and opportunities faced in piloting the program. We suggest that bringing creative arts therapy into queer spaces must be done through an anti-oppressive approach seeking to minimize power dynamics and increase safety. We must also create inclusive spaces that embrace intersectionality in order to provide safe, accessible, and empowering programs for LGBTQ+ individuals.